A Partial Solution of MoM Matrices Based on Characteristic Basis Functions and its Application to On-Board Antennas Positioning - Laviada, Jaime; Meana, Javier Gutiérrez-; Pino, Marcos R.; Heras, Fernando Las- (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A new technique, called incomplete Gauss-Jordan elimination (IGJE), is presented and hybridized with the characteristic basis function method (CBFM) to enable the partial solution of the method of moments (MoM) matrix. As a consequence, the goal of this technique is its application to optimization problems in electrically large scenarios where multiple but similar configurations need to be analyzed, since our method performs these analyses with a considerable reduction in the computational time and also memory. The term “similar” refers to the fact that the original structure is split into different blocks and modifications in the geometry (inserting, eliminating, or changing elements) of only a specific set of these blocks are allowed throughout the optimization process. In particular, we take advantage of this technique to analyze the optimum emplacement of an antenna on a given structure (e.g. a ship or airplane) with just one analysis. An example of an airplane antenna positioning is shown to illustrate the procedure.